Pengaruh Komitmen Organisasi, Independensi Terhadap Kinerja Auditor BPKP Kota Banda Aceh - Rahmah Yulianti; Cut Hamdiah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study was to examine the effect of organizational commitment and independency on auditor performance of Government of Internal Auditor. This study used questionnaire as an instrument to collect data. The questionnaires were distributed to auditors in the Government of Internal Auditor, Aceh Office. The number of respondents were 57 who were selected based on purposive sampling method. The data was analysed by using linear regression method. The result unveils that the organizational commitment and audit independency have significant effect on the Government of Internal Auditor.